Respuesta :
To answer this item, we may use the concept of substitution such that we substitute y of the second equation to y of the first equation.
2(6x - 2) = 3x - 14
Simplifying,
12x - 4 = 3x - 14
x = -10/9
Calculating for the value of y,
y = 6(-10/9) - 2
y = -26/3
The solution of the system of linear equation is then (-10/9, -26/3).
2(6x - 2) = 3x - 14
Simplifying,
12x - 4 = 3x - 14
x = -10/9
Calculating for the value of y,
y = 6(-10/9) - 2
y = -26/3
The solution of the system of linear equation is then (-10/9, -26/3).